Financial Management System - S.Meena, Ms; S.Girija, Mrs; S.Kayathri, Mrs (International Journal of Engineering and Technology, 2018)
The project entitled as â€œFinancial Management Systemâ€ The main objective is maintaining the company details and sends the daily report to the company manager. The admin can view the employee attendance details, employee registration details and sales details. This project contains two modules such as admin module and user modules. The admin can maintain employee details and sales details. In user modules, day by day update attendance details and product sales details in the system. So the admin can easily view product details and sales details and employee details in the system. The system can view day by day activities in the company process. The front end of the project is JSP and back end is MySQL.Â Â Â
Keywords: Employee Details; Sales Details; Product Details